Knowledge, attitude, acceptance, and practice of COVID-19 vaccination and associated factors complemented with constructs of health belief model among the general public in South Gondar, Ethiopia: A community-based study - Yisak, Hiwot; Ambaw, Birhanie; Belay, Emaway; Desalegn, Tsion; Getie, Adanech; Asrat, Meswat; Guangul, Asrate; Seid, Tigist; Zewde, Edgeit Abebe; Assefa, Mengesha; Ewunetei, Amien (Frontiers in Public Health, 2022)
Introduction: Understanding the epidemiological dynamics of disease control, as well as the effectiveness, compliance, and success of the vaccination program requires an understanding of the local population's knowledge, attitude, and practice regarding the Corona Virus Disease of 2019(COVID-19)vaccine. So the objective of this study was to assess knowledge, attitude, and practice toward COVID-19 vaccination and associated factors among the general public. Methods: A cross-sectional study was conducted in the South Gondar Zone, among residents above the age of 18 years. The study used objective measures and the constructs of the health belief model. Binary logistic regression was used and the result of the final model was presented in terms of adjusted odd ratio(AOR) and 95% confidence intervals(CI) and statistical significance was taken and considered at P-value less than 0.05. Results: The study was conducted on 1111 study participants. The Mean age is 30.83 ±7.106. About 575(51.8%) of the respondents have good knowledge about the COVID-19 vaccination and 43.4% have a positive attitude towards COVID -19 vaccination. About 361(32.5%) of the respondents were willing to take the vaccine if it is available and 113(10.2%) of them were vaccinated. Participants with a positive attitude and good knowledge, those with a secondary level of education AOR =5.70, 95 %CI(2.60-12.60), those with a monthly income of >2000birr AOR=6.30, 95 % CI(2.50-15.60), those having Television(TV), and those who use Facebook AOR =17.70, 95 % CI(10.10-30.90) had a higher level of acceptance of COVID -19 vaccination. The health belief model's constructs of perceived susceptibility AOR=1.53, 95 % CI (1.26-1.85), perceived benefit AOR=1.49, 95 % CI (1.28-1.75), and cues to action AOR=0.54, 95 % CI (0.45-0.65) were all linked to COVID-19 vaccine acceptability. Conclusion: The level of acceptance of COVID-19 vaccination is much lower. having a positive attitude score and good knowledge score, level of education, monthly income, Presence of TV, the